Asymmetric synthesis of 3, 3′-pyrrolidinyl-dispirooxindoles via a one-pot organocatalytic Mannich/deprotection/aza-Michael sequence. Issue 11 (4th January 2016) - Zhao, Kun; Zhi, Ying; Li, Xinyi; Puttreddy, Rakesh; Rissanen, Kari; Enders, Dieter
Abstract : A highly stereoselective synthesis of functionalized 3, 3′-pyrrolidinyl-dispirooxindole derivatives with three stereogenic centers, including two contiguous spiro-stereocenters, has been achieved through an organocatalytic Mannich/Boc-deprotection/aza-Michael sequence. Abstract : A highly stereoselective synthesis of functionalized 3, 3′-pyrrolidinyl-dispirooxindole derivatives with three stereogenic centers, including two contiguous spiro-stereocenters, has been achieved through an organocatalytic Mannich/Boc-deprotection/aza-Michael sequence. Employing the commercially available (DHQD)2 PHAL as the catalyst, the scalable reaction occurs with good yields and excellent stereoselectivities, providing a short entry into a series of 3, 3′-pyrrolidinyl-dispirooxindoles of potentially medical value.